2001
DOI: 10.3201/eid0701.010117
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Control and Multidrug-Resistant Pulmonary Tuberculosis in Female Patients, Lima, Peru

Abstract: Disease Control and Prevention, or the authors' affiliated institutions. Use of trade names is for identification only and does not imply endorsement by any of the groups named above.All material published in Emerging Infectious Diseases is in the public domain and may be used and reprinted without special permission; proper citation, however, is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
0
20
1
3
Order By: Relevance
“…However, it has been well recognized that the risk of TB transmission from unsuspected or unrecognized patients is likely far greater than the risk from known patients with TB, in large part because patients who are not yet diagnosed may more readily emit infectious aerosols than patients under effective treatment (27). Although there have been few comprehensive studies on the exact prevalence of unsuspected TB, a few surveys among general medical wards or emergency departments have revealed that approximately one-third of patients with TB may pass through the early stages of entry into hospital unsuspected (28,29). In high-burden settings with limited existing infection control resources, masks may be a relatively inexpensive yet effective initial measure through which to limit TB transmission, especially if offered and used short term by all patients presenting with prolonged cough or other symptoms suggestive of TB, for example.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been well recognized that the risk of TB transmission from unsuspected or unrecognized patients is likely far greater than the risk from known patients with TB, in large part because patients who are not yet diagnosed may more readily emit infectious aerosols than patients under effective treatment (27). Although there have been few comprehensive studies on the exact prevalence of unsuspected TB, a few surveys among general medical wards or emergency departments have revealed that approximately one-third of patients with TB may pass through the early stages of entry into hospital unsuspected (28,29). In high-burden settings with limited existing infection control resources, masks may be a relatively inexpensive yet effective initial measure through which to limit TB transmission, especially if offered and used short term by all patients presenting with prolonged cough or other symptoms suggestive of TB, for example.…”
Section: Discussionmentioning
confidence: 99%
“…461,462 464 Following the widely publicised and high-mortality outbreak of XDR tuberculosis at the Church of Scotland Hospital in KwaZulu-Natal, South Africa, a series of similar targeted interventions have dramatically reduced transmission in the hospital and in the community.…”
Section: Importance Of Unsuspected Drug Resistancementioning
confidence: 99%
“…Under high-burden conditions, TB is commonly missed in persons presenting with unrelated conditions (Willingham et al 2001;Bates et al 2012Bates et al , 2013. Under low-burden conditions, the diagnosis is less likely to be considered even with classical symptoms.…”
Section: Administrative Approaches To Tb Transmission Control Known Omentioning
confidence: 99%
“…Under low-burden conditions, the diagnosis is less likely to be considered even with classical symptoms. Studies in Peru and Africa have shown the prevalence of unsuspected TB in general medical settings, including smear-positive, drug-resistant cases (Willingham et al 2001;Bates et al 2012). …”
Section: Administrative Approaches To Tb Transmission Control Known Omentioning
confidence: 99%